The new rich in China : future rulers, present lives - Goodman, David S. G. (New York : Routledge, 2008)
Including sections on class, status and power, agency and structure and life style, this book develops the concept of the New Rich further in light of China's accelerated social change and the ever-increasing affluence of some of the population.
Why China has no new middle class: cadres, managers and entrepreneurs / David S.G. Goodman -- Class, stratum and group: the politics of description and prescription / Yingjie Guo -- Market transition, wealth and status claims / Xiaowei Xang -- Richer than before: the cultivation of middle class taste: education choices in urban China / Stephanie Hemelryk Donald and Zheng Yi -- Corporate CEOs as cultural promoters / Colin Hawes -- From coal black to hospital white: new welfare entrepreneurs and the pursuit of a cleaner status / Beatriz Carrillo -- Entrepreneurial women: personal wealth, local politics and tradition / Minglu Chen -- The professional middle classes: management and politics / Ivan Cucco -- Professors, doctors, and lawyers: the variable wealth of the professional classes / Jingqing Yang -- The forest city: homeownership and new wealth in Shenyang / Luigi Tomba and Beibei Tang -- The Shanghai-Hong Kong connection: fine jewelry consumption and the demand for diamonds / Carolyn Cartier -- Issue-based politics: feminism with Chinese characteristics or the return of bourgeois feminism? / Louise Edwards -- Men, women and the maid: at home with the new rich / Wanning Sun -- Advanced producers or moral polluters: China's bureaucrat-entrepreneurs and sexual corruption / Elaine Jeffreys.
Includes bibliographical references (p. [245]-291) and index.
Keywords: Middle class -- China; Wealth -- China; Social classes -- China; Social change -- China; Power (Social sciences) -- China